(untitled) (Journal of Nematode Morphology and Systematics, 2012)
A new species of Neodolichorhynchus (Mulkorhynchus) is described from soil around the roots of rose plant grown in the premises of University of Karachi, Sindh, Pakistan. Neodolichorhynchus (Mulkorhynchus) indicus sp. n. is characterized by having 12 longitudinal ridges, posterior vulva (V = 59-61), bilobed spermatheca, tail terminus without annuli in female, and bursa not recurved at tail tip. Its more relevant morphometrics are: body length 706-810 μm, a = 27-40, b = 4.7-6.0, c = 22-24, stylet 16-18 μm long, spicules 18-21 μm long and gubernaculum 7-14 μm long. A compendium of the subgenus Neodolichorhynchus (Mulkorhynchus) is also provided as well as a key to identification of its species.